A Two-Dimensional Instability In Mixed Convection With Spatially Periodic Lower Wall Heating By LBM Method - Raheela Manzoor; Zahid Ahmad; Irfan Ali; Farida Aslam (Kurdish Studies, 2024)
Numerical study for 2-D mixed convection (MC) flow at bottom heated wall has been carried out through lattice Boltzmann method (LBM) using periodic boundary condition. The uniform temperature is applied at top surface by considering zero temperature and velocity conditions initially throughout the channel. This study based to compare the results of flow structure obtained by using numerical techniques i.e. lattice Boltzmann method under the influence of non-dimensional parameters such as Rayleigh (Ra), Prandtl (Pr) and Reynolds numbers (Re) on vertex flow characteristics and its stability behavior. Different flow structures have been observed by using different ranges of Re and Ra numbers, while keeping Pr number fix (i.e. Pr = 1). It is investigated that at some range of Re and Ra, the results obtained are in good agreement with Tangborn results. Furthermore, it is investigated that the separation vortex generated at downstream of hot wall has point of inflection in flow, which leads towards instability and its motion is representing an unstable travelling wave (stream wise instability) behavior at high range of Re and Ra numbers. The results are shown in terms of streamlines, isotherms and time-trace analysis of inflow velocity.